The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006 IEEE International Conference on Multimedia and Expo 2006
DOI: 10.1109/icme.2006.262442
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Strategies for Active Learning in Personal Photo Retrieval

Abstract: With the advent and proliferation of digital cameras and computers, the number of digital photos created and stored by consumers has grown extremely large. This created increasing demand for image retrieval systems to ease interaction between consumers and personal media content. Active learning is a widely used user interaction model for retrieval systems, which learns the query concept by asking users to label a number of images at each iteration. In this paper, we study sampling strategies for active learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…Considering the Corel database, we find in our experiments that only 7% of the images generates errors for all strategies. Indeed, theoretically it should be possible to decrease considerably the error rate, maybe by alternating or combining strategies like in [16], or by defining other strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the Corel database, we find in our experiments that only 7% of the images generates errors for all strategies. Indeed, theoretically it should be possible to decrease considerably the error rate, maybe by alternating or combining strategies like in [16], or by defining other strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Cohn et al have demonstrated its usefulness in theory [8]. Wu et al define a representativeness measure for each sample according to its distance to nearby samples, and take it as a criterion of sample selection [18]. Zhang et al estimate data distribution p(x) by Kernel Density Estimation (KDE), and then take it into account in sample selection [13,20].…”
Section: Densitymentioning
confidence: 99%
“…Thus, in practice most active learning methods empirically adopt closest-to-boundary criterion to choose the most uncertain samples [23,24]. Zhang et al and Wu et al further proposed to incorporate the density distribution of samples into the sample selection process [29,32]. Brinker et al [4] pointed out that the selected samples should be diverse, especially when the active learning method works in a batch mode, i.e., in each round a batch of samples rather than an individual sample is selected.…”
Section: Related Workmentioning
confidence: 99%
“…(1) we can also see the impact of p(x). Wu et al define a representativeness measure for each sample according to its distance to nearby samples, and take it as a criterion of sample selection [29]. Zhang et al estimate data distribution p(x) by Kernel Density Estimation (KDE), and then use it in sample selection [17,32].…”
Section: Densitymentioning
confidence: 99%